Complete Chloroplast Genome Sequence of Hibiscus cannabinus and Comparative Analysis of the Malvaceae Family - Cheng, Yan; Zhang, Liemei; Qi, Jianmin; Zhang, Liwu (Frontiers in Genetics, 2020)
Kenaf (Hibiscus cannabinus) is one of the most fast-growing bast in the world and belongs to the family Malvaceae. However, the systematic classification and chloroplast (cp) genome of kenaf has not been reported to date. In this study, we sequenced the chloroplast genome of kenaf and conducted phylogenetic and comparative analyses in the family of Malvaceae. The sizes of H. cannabinus cp genomes were 162,903 bp in length, containing 113 unique genes (79 protein-coding genes, four rRNA genes, and 30 tRNA genes). Phylogenetic analysis indicated that the cp genome sequence of H. cannabinus has closer relationships with Talipariti hamabo and Abelmoschus esculentus than with H. syriacus, which disagrees with the taxonomical relationship. Further analysis obtained a new version of the cp genome annotation of H. syriacus and found that the orientation variation of SSC (Small Single Copy) region exists widely in the family of Malvaceae. The highly variable ycf1 and the highly conserved gene rrn32 were identified among the family of Malvaceae. In particular, the explanation for two different SSC orientations in the cp genomes associated with phylogenetic analysis is discussed. These results provide insights into the systematic classification of the Hibiscus genus in the Malvaceae family. Keywords: Hibiscus cannabinus; Malvaceae; Gene orientation; SSC (Small Single-Copy); LSC (Large Single-Copy); cp (Chloroplast)